Development of a Novel Ionic Liquid Based Microemulsion System for Gemcitabine Hydrochloride and in vitro Evaluation in Human Cervical Cancer HeLa Cells - Chen, Yuanyuan; Li, Juan (Indian Journal of Pharmaceutical Education and Research, 2021)
Aim: The aim of this study was to develop novel ionic liquid based microemulsion systems and assessing the in vitro activity against HeLa cancer cell line. Materials and Methods: Four imidazaolium cation based ionic liquids were synthesized and used in the studies. The microemulsions were developed and optimized after studying the phase diagrams comprising isopropyl myristate and different surfactant combinations. The physical characteristics of the prepared formulations were determined by studying globule size, polydispersity index and zeta potential. Also, morphology was studied using transmission electron microscopy. Ex vivo drug release was studied using porcine skin and in vitro evaluation was performed in HeLa cell line. Results: The microemulsions exhibited desirable physical and morphological characteristics. Furthermore, excellent drug release profiles and adequate drug tissue retention were established in ex vivo permeation studies performed using porcine vaginal tissues. The results of cytotoxicity studies revealed that the ionic liquid based microemulsions had noticeably improved potency than conventional w/o microemulsions. Conclusion: Ionic liquid based microemulsion systems were prepared for gemcitabine. Although our preliminary evaluation has shown promising results, deeper insights on their therapeutic potential needs to be studies by means of detailed toxicity evaluation and in vivo studies.
Keywords: Gemcitabine; Microemulsion; Ionic liquid; Cervical cancer; Drug delivery